Lithium reduces the span of G protein‐activated K+ (GIRK) channel inhibition in hippocampal neurons. (12th September 2017) - Dascal, Nathan; Rubinstein, Moran
Abstract: Objectives: Lithium (Li + ) is one of the most widely used treatments for bipolar disorder (BD). However, the molecular and neuronal basis of BD, as well as the mechanisms of Li + actions are poorly understood. Cellular and biochemical studies identified G proteins as being among the cellular targets for Li + action, while genetic studies indicated an association with the KCNJ3 gene, which encodes the G protein‐activated inwardly rectifying K + (GIRK) channels. GIRK channels regulate neuronal excitability by mediating the inhibitory effects of multiple neurotransmitters and contribute to the resting potassium conductance. Here, we explored the effects of therapeutic dose of Li + on neuronal excitability and the role of GIRK channels in Li + actions. Methods: Effects of Li + on excitability were studied in hippocampal brain slices using whole‐cell electrophysiological recordings. Results: A therapeutic dose of Li + (1 mM) dually regulated the function of GIRK channels in hippocampal slices. Li + hyperpolarized the resting membrane potential of hippocampal CA1 pyramidal neurons and prolonged the latency to reach the action potential threshold and peak. These effects were abolished in the presence of tertiapin, a specific GIRK channel blocker, and at doses above the therapeutic window (2 mM). In contrast, Li + reduced GIRK channel opening induced by GABAB receptor (GABAB R) activation, causing reduced hyperpolarization of the membrane potential, attenuated reduction of input resistance, and a smaller decrease of neuronal firing. Conclusions: A therapeutic dose of Li + reduces the span of GIRK channel‐mediated inhibition due to enhancement of basal GIRK currents and inhibition of GABAB R evoked responses, providing an important link between Li + action, neuronal excitability, and cellular and genetic targets of BD.